2020
DOI: 10.1097/md.0000000000022608
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological characteristics and profile of drug-resistant tuberculosis among children with tuberculosis in Sichuan, China, 2015–2018

Abstract: The aim of this study was to investigate the epidemiological characteristics and profile of drug-resistant tuberculosis (DR-TB) among children with TB in Sichuan province of China. From January 2015 to December 2018, microbiological culture-confirmed child TB cases (aged <15 years old) were enrolled retrospectively. Epidemiological and clinical information from these cases, and the drug susceptibility testing results of the isolates were collected and analyzed. Of 317 culture-confirmed ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previous studies have indicated that BCG vaccination could decrease the risk of severe TB. 45 In our study, the distribution of BCG vaccination was different in the MDR and DS groups, and BCG vaccination was a protective factor against MDR-TB in children. However, this result might be caused by 100% of patients in the MDR group having severe TB.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have indicated that BCG vaccination could decrease the risk of severe TB. 45 In our study, the distribution of BCG vaccination was different in the MDR and DS groups, and BCG vaccination was a protective factor against MDR-TB in children. However, this result might be caused by 100% of patients in the MDR group having severe TB.…”
Section: Discussionmentioning
confidence: 51%
“…[ 26 ] In recent years, the multi-drug resistance rates of DR-TB in children reported in various parts of China have been lower than the reporting level from 2005 to 2012. [ 5 , 8 , 17 ] The results of this study also showed that the DR resistance rate in Sichuan decreased in the past 5 years, indicating that the normal treatment for tuberculosis in children in the past 5 years showed a good therapeutic effect, but also reflected the importance of prevention and control in children. However, there was no significant downward trend in the rate of multi-drug resistance in the past 5 years, and it is necessary to further strengthen the understanding of actively carrying out drug resistance examination in newly diagnosed children, timely develop standardized drug resistance regimens, and improve the cure rate.…”
Section: Discussionmentioning
confidence: 56%
“…[ 7 ] A retrospective study on the epidemiological characteristics and characteristics of DR-TB in children with tuberculosis in Sichuan Province from 2015 to 2018 showed that the culture-confirmed tuberculosis in children accounted for 3% of all new tuberculosis cases, which was lower than the estimated proportion of tuberculosis in children in China, with the overall rate of DR-TB at 24.3% and the rate of MDR-TB at 5.4%. [ 8 ] The analysis by Zignol et al [ 9 ] found that the risk of MDR-TB was similar in children between under 5 years and 5 to 14 years of age. It is important to pay attention to the diagnosis and prevention of tuberculosis and drug resistance in children for disease control.…”
Section: Introductionmentioning
confidence: 99%
“… 17 A retrospective study by Xu et al using data between 2015 and 2018 in Chengdu, Sichuan Province, found a drug resistance rate of 24.3% for pediatric TB. 18 A meta-analysis by DiNardo which included 9 studies showed that a total of 939 children with suspected TB had a positive MGIT 960 culture detection rate of 24.4% (229/939), including 22.03% (154/699, median 21.1%, IQR 14.5–38.4%) in children under 5 years and 35.57% in children 5–15 years (69/194, median 31.5%, IQR 23.8–43.4%). 19 Another multicenter study of EPTB in children in mainland China showed a bacteriological positivity rate of 29.88% (401/1342).…”
Section: Discussionmentioning
confidence: 99%